Role of DNA-dependent protein kinase in recognition of radiation-induced DNA damage in human peripheral blood mononuclear cells - Frasca, D; Barattini, P; Tocchi, G; Guidi, L; Pierelli, L; Doria, G (International immunology, 2001)
The DNA-dependent protein kinase (DNA-PK) complex plays a crucial role in radiation-induced DNA damage recognition. The complex includes the ku heterodimer, which comprises ku 70 and ku 80 subunits, that binds DNA termini of breaks without sequence specificity, and the catalytic subunit DNA-PKCS: The activation of the DNA-PK complex was studied in X-irradiated peripheral blood mononuclear cells (PBMC) from subjects of different ages. Radiation-induced changes in the DNA-binding activity of the ku heterodimer, and in the concentrations of ku 70, ku 80, DNA-PKcs and phosphorylated ku 80 were determined in nuclear and cytoplasmic extracts. DNA-binding activity was increased by irradiation only in the nuclear extract of PBMC from young, but not from elderly subjects, whereas it was found unchanged in cytoplasmic extracts regardless of age. The radiation-induced activation of the DNA-PK complex may result from the increased concentrations of ku 80 and DNA-PKcs in the cytoplasm of PBMC from young, but not from elderly subjects, leading to a higher concentration of phosphorylated ku 80 which readily migrates to the nucleus where, after dimerization with ku 70, binds to DNA breaks. These findings suggest major steps involved in DNA-PK activation, and the intracellular and molecular changes that may account for the age-dependent impairment of DNA repair capacity in irradiated mammalian cells.